Legal protection for women from violence: Analytical Theory Study - Abdullah, Muhammad Qasim; Alawi, Moh Araq (Al-Adab Journal, 2022)
Violence is one of the first manifestations of behavior known to human societies. But it has known a great increase in recent decades, and almost no society is devoid of some of its forms that societies have known since ancient times, but some of its causes are linked to some characteristics of modern society, especially those that seem to express pressures and feelings of frustration and oppression. The protection of women from violence is the cornerstone that can be built upon to protect them from discrimination and persecution and to advance their reality as a prelude to an active and constructive contribution to the development process, as marginalized, abused and violated women’s rights constitute a stumbling block against any attempt to change or develop in the state. The research reached the following most important results: The lack of laws that protect women from violence, is one of the factors leading to an increase in violence against them. There is no psychological, social and legal support for battered women. Women’s knowledge of their rights reduces violence directed at them. Women in Iraq live in fear of violence with the intensification of conflict and the escalation of security disturbance. their rights and legal protection for them.